Watching Life and Death at a Cellular Level - Ross, Rachel; Tourville, Claudia; Rigden, Gabrielle; Lewis, David E.; Bailey-Hartsel, Scott (My University, 2017)
The purpose of this study was to show that the poorly-tolerated antifungal drug Amphotericin B (AmB) causes collateral damage in human cells in part by depolarizing (short-circuiting) mitochondria, the powerhouses of the cell.
Color poster with text, images, graphs, and models.
Keywords: Antifungal drugs; Biochemistry; Molecular biology; Cells; Posters